2022
DOI: 10.7717/peerj.12724
|View full text |Cite
|
Sign up to set email alerts
|

miR-148a-3p inhibits the proliferation and migration of bladder cancer via regulating the expression of ROCK-1

Abstract: Purpose To investigate the mechanism of miR-148a-3p regulating the proliferation and migration of bladder tumor cells. Materials and Methods We conducted a preliminary study to detect the relative expression of miR-148a-3p in bladder cancer and para-cancerous tissue samples. Three bladder tumor cell lines, T24, 5,637 and UM-UC-3, were selected. The expression levels of miR-148a-3p were artificially regulated with miR-148a-3p mimics and the miR-148a-3p inhibitor. The relative expression levels of miR-148a-3p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…RhoA regulates the epithelial barrier not only through ROCK alone but also scaffold proteins such as rhophilin, rhotekin, kinectin, and mDia, and serine/threonine protein kinases such as PKN and citron kinase . ROCK is also regulated by Piezo1, Coronin1A/B, and miR-148a-3p, among others. Neither Rosin nor Y-27632 alone could indicate that DON-mediated damage to the intestinal epithelial barrier is through the RhoA/ROCK pathway. So for the accuracy of the study, we used both Rosin and Y-27632 separately.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA regulates the epithelial barrier not only through ROCK alone but also scaffold proteins such as rhophilin, rhotekin, kinectin, and mDia, and serine/threonine protein kinases such as PKN and citron kinase . ROCK is also regulated by Piezo1, Coronin1A/B, and miR-148a-3p, among others. Neither Rosin nor Y-27632 alone could indicate that DON-mediated damage to the intestinal epithelial barrier is through the RhoA/ROCK pathway. So for the accuracy of the study, we used both Rosin and Y-27632 separately.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is reported to be over-expressed in up to 85% of SACC, making it a therapeutic target of interest [39]. Recent studies have shown that EGFR is abnormally over-expressed in metastatic SACC and is a key regulatory molecule for SACC metastasis [40]. Prior studies have targeted the EGFR pathway via numerous therapeutic agents including ge tinib [41], cetuximab [42], and lapatinib [43] without meaningful response rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our data advise that circFTO regulates NSCLC proliferation and migration via sponge miR-148a-3p, which could inhibit tumorigenesis development. Xu et al reported that miR-148a-3p suppresses bladder cancer proliferation and migration via regulating Roc-1 expression [ 35 ]. Zeng et al found that circANKS1B regulates breast cancer by promoting the transcription factor UF1 expression via the sponge miR-148a-3p [ 36 ].…”
Section: Discussionmentioning
confidence: 99%